Laser cooling of high temperature superconductors - Dietrich, A (2019)
In this dissertation, we theoretically demonstrate laser light induced control and cooling over the order parameter of superconducting cuprates. We predict a non-equilibrium state with enhanced robustness against thermal fluctuations when pumped with coherent pulses. This might ultimately increase the critical temperature of the cuprate. In particular, we propose a parametric cooling scheme for a bilayer cuprate modelled phenomenologically as a stack of long intrinsic Josephson junctions. We identify a parameter regime, which according to the switching current distribution allows a reduction of the effective system temperature by approximately 25%. This cooling scheme suppresses the thermal excitation of Josephson vortices. This might lead to an indirect mechanism for controlling topological excitations in the phase of the superconducting order parameter. We further find that the strong driving of the cuprates can lead to parametric instabilities. To investigate the effect strong driving can have on the dissipative dynamics, we derive a FloquetMarkov master equation. We find that strong driving is a measure for probing the bath spectral density of otherwise inaccessible condensed matter systems.